Classification of Attack for IDS Using Binary Genetic Algorithm Based Feature Selection - Rani, S (International Journal of Computer Sciences and Engineering, 2025)
IDS is used to detect any kinds of attacks that may harm the safety of systems. A capable IDS system needs low FAR, and high accuracy. In this paper, we have used fully distinct DM approaches on IDS with the KDD data set. Here the BGA which offers a new method used for fixing normal & DOS.